Performance optimization of a heat pump integrated with a single-screw refrigeration compressor with liquid refrigerant injection. (15th September 2020) - Wen, Qiangyu; Zhi, Ruiping; Wu, Yuting; Lei, Biao; Liu, Shanwei; Shen, Lili
Abstract: Refrigerant injection is a good method for reducing the exhaust temperature of a single-screw refrigeration compressor (SSRC). In this paper, an accurate method is proposed to calculate the variation of the injection area for different initial positions and different sizes of injection holes. Furthermore, a mathematical model describing the internal working process of an SSRC with liquid refrigerant injection (LRI) is established to evaluate the performance of an SSRC and heat pump with a variety of injection hole geometries and working conditions. This theoretical model is verified by comparing the calculation results with experimental data. The results show that LRI can markedly reduce the exhaust temperature and improve the performance of the SSRC and heat pump to some extent. The injection-hole radius is the most important factor affecting the performance of the compressor and heat-pump system. The variations of different performance parameters of the SSRC and heat pump at low ambient temperature can be obtained. This work provides a theoretical method for optimizing the injection process in SSRCs. Highlights: A mechanical model is proposed to accurately calculate the injection area of the SSRC. A mathematical model is developed to study the performance of compressor with LRI. The performance of heat pump with liquid refrigerant injection is experimentally studied. The effects of the different injection parameters on the performance of the heat pump are compared.